THE NOTION OF SEMANTICS AND LEXICOLOGY - Melikulova Madina Khikmatovna (Western European Studies, 2024)
This article deals with exploring the branches of linguistics, namely semantics and lexicology. The prime aim of research implementing detailed information and full notions to these terms. On the top of that, the functions of semantics and lexicology, as well as the role of them are written in article
Keywords: semantics; lexicology; function; meaning